UPAYA MENINGKATKAN HASIL BELAJAR MATERI TEKNIK DASAR PASSING BAWAH BOLA VOLI DENGAN PEMBELAJARAN KOOFERATIF MELALUI MEDIA VIDIO PEMBELAJARAN PADA SISWA KELAS 7 D SMP NEGERI 3 ABIANSEMAL TAHUN PELAJARAN 2020/2021 - Desak Nyoman Tri Widiawati (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
Volleyball is a type of team sport game in which each team is played by two teams where each team consists of six people on a field measuring 9 square meters for each team separated by a net or net. The purpose of this study was to improve learning outcomes of basic volleyball bottom passing techniques with cooperative learning through sports learning video media. This type of research is classroom action research. The subject of the research was the action research of grade 7 D students of SMP Negeri 3 Abiansemal for the academic year 2020/2021, and the object of research was the basic technique of passing down volleyball. In this study, two cycles were used and each cycle went through four stages of the activity process which included (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. The results of the study that learning passing down through cooperative learning methods in students for 2 cycles can improve student learning outcomes. The average result of the volleyball bottom passing skill in the Pre-cycle with a total score of 2,090.67 with an average of 65.55 and the first cycle with an average score of 2,443.67 with an average of 76.36 so that there is an increase of 11.03 . Likewise for the second cycle with an average score of 2,670 with an average of 83.44 so that from cycle I to cycle II there was an increase of 7.08.